2022
DOI: 10.3389/fmicb.2022.897656
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis of the genus Leuconostoc

Abstract: Leuconostoc is a genus of saccharolytic heterofermentative lactic acid bacteria that inhabit plant-derived matrices and a variety of fermented foods (dairy products, dough, milk, vegetables, and meats), contributing to desired fermentation processes or playing a role in food spoilage. At present, the genus encompasses 17 recognized species. In total, 216 deposited genome sequences of Leuconostoc were analyzed, to check the delineation of species and to infer their evolutive genealogy utilizing a minimum evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The subset consisting of the ANI-confirmed P. mirabilis ( n = 1,883) was visualized as a heatmap in RStudio with a gradient centered at 98% ( 24 ). This cutoff was previously used for subspecies delineation of Salmonella , Mycobacterium abscessus, and Leuconostoc lactis ( 25 - 27 ). Subspecies classification was defined by Cytoscape reciprocal groups composed of genomes with ANI > 98% to other genomes within the group but 98% < ANI > 95% between groups.…”
Section: Methodsmentioning
confidence: 99%
“…The subset consisting of the ANI-confirmed P. mirabilis ( n = 1,883) was visualized as a heatmap in RStudio with a gradient centered at 98% ( 24 ). This cutoff was previously used for subspecies delineation of Salmonella , Mycobacterium abscessus, and Leuconostoc lactis ( 25 - 27 ). Subspecies classification was defined by Cytoscape reciprocal groups composed of genomes with ANI > 98% to other genomes within the group but 98% < ANI > 95% between groups.…”
Section: Methodsmentioning
confidence: 99%
“…However, compared with C1, C2 and C3, the dominant genus of the C4 sample was Pseudomonas with relative abundances up to 54% (Figure 1D). Lactococcus and Leuconostoc were detected in the camel milk samples at levels of 6%, 106%, 14% and 2%, respectively, which are fermentor strains that produce flavor during milk fermentation and improve the quality of dairy products [24,25]. Chryseobacterium was also found in all camel milk samples with relative abundances of 1.58%, 2.86%, 1.67% and 1.14%, respectively (Figure 1D).…”
Section: The Bacterial Community Structure Of Camel Milkmentioning
confidence: 97%
“…Moreover, the study concluded that analyzing the intraspecies ANI and conserved genes was not enough to discriminate the four subspecies within the Leuconostoc mesenteroides (Raimondi et al, 2022).…”
Section: F I G U R Ementioning
confidence: 98%
“…found that the minimal phylogenetic trees reconstructed based on core‐genes and ANI, but not single‐gene (especially 16S rRNA gene), showed similar topologies, giving inconsistent phylogenetic signals and hindering clade‐ and species‐level classification. Moreover, the study concluded that analyzing the intraspecies ANI and conserved genes was not enough to discriminate the four subspecies within the Leuconostoc mesenteroides (Raimondi et al., 2022).…”
Section: Classification and Reclassification Of Lab In The Genomics Eramentioning
confidence: 99%